Sara Jammaśedajī Bāroneṭa, īāne, Sara Jammaśedajī Jījībhāīnī jīndagīno ane nevaṇṇanāṃ moṭāṃ puṇanāṃ ane dharamātu kammono ehevāla - Manaśukha, Manacerajī Kavasajī, fl. 1850-1900 (Daphatara Āśakāra Chāpākhānnāmmāṃ, 1891)
Biography of Sir Jammaśedajī Jījībhāī, 1783-1859, a philanthropist and first Indian knighted by the British.